The end of interpretation : reclaiming the superiority of ecclesial exegesis - Reno, Russell R., 1959- (Grand Rapids, MI. Baker Academic, 2022)
Those who wish to interpret and understand the Bible face a fundamental question: How do I interpret Scripture faithfully? Theological interpretation is an approach that has received much attention in recent years, and R. R. Reno is a leading practitioner and proponent of this approach. In The End of Interpretation, Reno's first full statement on the topic, he argues that Scripture is interpreted correctly only when it is read through the lens of creedal orthodoxy--that is, through the apostolic faith. The principle of accordance between doctrine and Scripture is of first importance for solid Christian interpretation. Reno provides a simple explanation of this multifaceted approach. He wrestles with what makes interpretation "theological" and provides two historical case studies, discussing Origen and the Reformation debate over justification. He then demonstrates what theological interpretation looks like in practice, reflecting on Genesis 1, John 17, and 1 Corinthians. Reno's insights will benefit serious readers who seek to interpret Scripture faithfully.
Includes bibliographical references and index.
Keywords: Bible -- Criticism, interpretation, etc; Criticism, interpretation, etc